Pembuatan Alat Pengering Cocopeat dengan Sistem Hybrid Berbasis Panel Surya - Pande Putu Agus Santoso; Iklas Sanubary; Diah Mahmuda (Jurnal Engine: Energi, Manufaktur, dan Material, 2022)
The purpose of this study was to describe the process and results of making cocopeat dryers with a hybrid system based on solar panels. This research was conducted with a tool development method consisting of five steps, namely literature study, design, tool and material preparation, manufacturing, and functional tests. The study results were (1) the process of making cocopeat dryers with a hybrid system based on the solar panel was the calculation of solar panel components, frame making, coating of frames with the casing, assembling of electronic components, and functional tests. (2) The cocopeat dryer with a hybrid system based on solar panels that have been made has dimensions of 120 cm in length, 60 cm in width, and 130 cm in height—equipped with a 100 Wp solar panel, a 12 V 65Ah dry battery, a 600 W inverter, three 15W halogen lamps, and a 22W fan. (3) The functional test results show that the average temperature inside the dryer is 52.84oC, 8.56oC higher than the temperature outside the tool. The average humidity inside the dryer is 23.4%, 17.2% lower than the humidity outside the appliance.